O papel do cooperado no processo de construção da Copagril - Favarim, Eliane Aparecida (2010)
This work is dissertational result of a procedure of investigation, description and analysis of a case study. To this end, the object of research focuses on the relationship developed by the cooperative in the formation and development of Cooperativa Agroindustrial Copagril Rondon - Paraná. Our leadership in this development methodology, conducted the overall goal to learn, understand and analyze the movement of insertion of members of Copagril in decision-making in the cooperative condition. We directed our research while addressing the problem - to what extent, to assume the personality of cooperating in Copagril guarantees to members participating in decisions in effect deliberative spaces. We develop our thesis based on bibliographical research and the use of instrumental interview. We defined and selected 25 interviews as research subjects themselves members. This academic study referred us to the following conclusion: The Copagril acts vying for their market niche. Their decisions are taken in the same way the other competitors. Thus, farmers trigger movements of non-cooperative loyalty, denying founding elements of the meaning of cooperation.